Pollen record in the northwestern continental shelf of the South China sea in the past 82 ka: Paleoenvironmental changes in the last glacial period. (1st September 2020) - Yu, Shaohua; Zheng, Zhuo; Harff, Jan; Chen, Fang; Jing, Xia; Zhou, Yang; Chen, Hongjun; Karolina, Bloom; Ryszard, Borówka
Graphical abstract: Highlights: Pollen from sediments in the northwestern shelf of the SCS were mainly derived from the Yungui and Tibetan Plateaus. Arboreal trees were dominated between MIS5a and MIS1, including the glacial period. High contributions of Pinus and lowland trees indicate a warm, wet climate in MIS3. Abstract: The northwestern continental shelf of the South China Sea (SCS) is in a geographic location that was sensitive to the global paleoenvironmental change during the last glacial period. Here we present a high resolution palynological record of Core ZBW (100.65 m in length) from the continental shelf of the SCS in the past 82 ka. In contrast to results for the northern SCS, the core's pollen assemblage was dominated by arboreal trees between MIS5a and MIS1, even during the glacial period. Pollen provenance analyses indicated it was mainly from the drainage basin of the Red River, the Yungui Plateau and Tibetan Plateau. Between 66 and 64 ka, the contribution of Pinus fell while that of Cyclobalanopsis and trilete spores increased, indicating a drier and cooler climate. Conversely, during MIS3, the contributions of Pinus and lowland trees were high, indicating a warm and wet climate. The sedimentary environment in core ZBW alternated between coastal marine and river alluvial or shore facies. A sedimentary hiatus between 42 and 13 ka coincided with a significant fall in sea levels. Seismic data indicate that the Hainan paleo-river Delta (HPRD) process occurred at the core site between 65 and 56 ka, with extremely high rates of sediment deposition. Pollen data indicate the HPRD process was coincided with a transition period from cooler and drier climate to warmer and wetter climate, and lower sea levels to higher sea levels.